Satellite image 1:500 000 Ritscherhochland, Ahlmannryggen, Jutulstraumen, Neuschwabenland, Antarktis - Brunk, Karsten (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie) Frankfurt am Main, 1986)
Landsat-2 imagery, supplemented with geographical names, 184/111, 30 October 1975; Annex 8 of 17, Brunk, K. (1986); Scale: 1:500000; Bounding Box: POLYGON ((-3.16 -70.7, 1.35 -71.5, -1.17 -72.93, -6 -72, -3.16 -70.7))